2011
DOI: 10.1111/j.1872-034x.2010.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Classification and characteristics of interferon‐related diabetes mellitus in Japan

Abstract: Potent combination therapy with PEG-IFN and ribavirin is likely associated with the increase in IFN-related type 1 diabetes. The combined measurement of GAD antibody and HLA-typing could be an effective strategy to predict the onset of type 1 diabetes associated with IFN therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…However, type 1 diabetes had a longer incubation period than previously reported, ranging from 10 days to 14 years 63 . In this study, males were more likely to develop interferon-associated type 2 diabetes ( Table 1 ), consistent with Kazuhisa Muraishi’s study 38 . One possible explanation for its sex-specific frequency was that visceral obesity was the leading cause of insulin resistance, and visceral obesity was associated more often with men 64 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, type 1 diabetes had a longer incubation period than previously reported, ranging from 10 days to 14 years 63 . In this study, males were more likely to develop interferon-associated type 2 diabetes ( Table 1 ), consistent with Kazuhisa Muraishi’s study 38 . One possible explanation for its sex-specific frequency was that visceral obesity was the leading cause of insulin resistance, and visceral obesity was associated more often with men 64 .…”
Section: Discussionsupporting
confidence: 91%
“…This study summarized the clinical and laboratory characteristics of 66 patients with interferon-associated diabetes. Here, our study showed that interferon-associated type 1 diabetes was reported worldwide from 1992 to 2020 far more than type 2 diabetes, which was consistent with Kazuhisa Muraishi’s conclusion 38 . The incidence of T1DM in hepatitis C patients treated with interferon was 10–18 times that of the general population 5 9 58 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A putative role of type I IFNs in systemic IR was suggested a long time ago in a study wherein IR developed in human subjects injected with IFN-a (59). Pegylated IFN-a therapy in patients with hepatitis C viral infection was also found to be associated with IR (60,61). Genetic deficiency of IRF7 (IFN regulatory factor 7), the critical transcription factor for induction of type I IFNs in pDCs (62), was found to protect mice from HFD-induced metabolic syndrome (63).…”
Section: Discussionmentioning
confidence: 99%